2016
DOI: 10.18632/oncotarget.13483
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations, expression and interaction networks in human cancers

Abstract: Although the associations of p53 dysfunction, p53 interaction networks and oncogenesis have been widely explored, a systematic analysis of TP53 mutations and its related interaction networks in various types of human cancers is lacking. Our study explored the associations of TP53 mutations, gene expression, clinical outcomes, and TP53 interaction networks across 33 cancer types using data from The Cancer Genome Atlas (TCGA). We show that TP53 is the most frequently mutated gene in a number of cancers, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 49 publications
(53 reference statements)
8
107
2
Order By: Relevance
“…P53 plays important roles in regulating the cancer-associated pathways such as cell cycle, apoptosis, DNA damage repair, autophagy, metabolism, inflammation, epithelial–mesenchymal transition (EMT), angiogenesis, and metastasis [50]. Accordingly, TP53 mutations often result in disturbances of the pathways regulated by p53 [58]. Indeed, we found that a number of p53-regulated pathways showed significantly differential activities between TP53 -mutated and TP53 -wildtype BCs such as the p53, cell cycle, apoptosis, Jak-STAT, NOD-like receptor, glycolysis, and Wnt pathways showing significantly higher activities in TP53 -mutated BCs than in TP53 -wildtype BCs (Mann-Whitney U test, P<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…P53 plays important roles in regulating the cancer-associated pathways such as cell cycle, apoptosis, DNA damage repair, autophagy, metabolism, inflammation, epithelial–mesenchymal transition (EMT), angiogenesis, and metastasis [50]. Accordingly, TP53 mutations often result in disturbances of the pathways regulated by p53 [58]. Indeed, we found that a number of p53-regulated pathways showed significantly differential activities between TP53 -mutated and TP53 -wildtype BCs such as the p53, cell cycle, apoptosis, Jak-STAT, NOD-like receptor, glycolysis, and Wnt pathways showing significantly higher activities in TP53 -mutated BCs than in TP53 -wildtype BCs (Mann-Whitney U test, P<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Large‐scale cancer genomics projects like International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA) provide opportunities for the integrative analysis in pan‐cancer at multiple omics levels (Gong et al., ). TP53 (OMIM *191170) was reported as the most frequently mutated gene in diverse cancers, and patients with TP53 mutation tend to have worse prognosis (Wang & Sun, ). Kandoth et al.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale cancer genomics projects like International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA) provide opportunities for the integrative analysis in pan-cancer at multiple omics levels (Gong et al, 2017). TP53 (OMIM *191170) was reported as the most frequently mutated gene in diverse cancers, and patients with TP53 mutation tend to have worse prognosis (Wang & Sun, 2017). Kandoth et al investigated 127 significantly mutated genes in 12 cancers and categorized them into 20 cellular processes, including Wnt/β-catenin, MAPK, and PI3K signaling pathways (Kandoth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We identified a set of candidate synthetic lethal (SL) genes [38] for 31 immune genes from above results. 19 SL genes for 6 immune genes have been found in mutation data (Table 3).…”
Section: Resultsmentioning
confidence: 99%